The modulation of delta responses in the interaction of brightness and emotion - Kurt, Pinar; Eroğlu, Kübra; Kuzgun, Tubanur Bayram; Güntekin, Bahar (Elsevier Science Bv, 2017)
The modulation of delta oscillations (0.5-3.5 Hz) by emotional stimuli is reported. Physical attributes such as color, brightness and spatial frequency of emotional visual stimuli have crucial effect on the perception of complex scene. Brightness is intimately related with emotional valence. Here we explored the effect of brightness on delta oscillatory responses upon presentation of pleasant, unpleasant and neutral pictures. We found that bright unpleasant pictures elicited lower amplitude of delta response than original unpleasant pictures. The electro-physiological finding of the study was in accordance with behavioral data. These results denoted the importance of delta responses on the examination of the association between perceptual and conceptual processes while in the question of brightness and emotion.
WOS: 000393245600001
PubMed ID: 27871912
Keywords: Delta; Brightness; Luminance; Emotion; IAPS